A microscopic swarm model simulation and fractal approach towards swarm agent behaviour - Widyarto, Setyawan; Abd. Latiff, Muhammad Shafie (International Journal of Computer Science and Network Security, 2006)
This research presents a simulation of a microscopic swarm model. The model represents detailed interaction of agents to control their movement in any agent arena. A physical based microscopic agent simulation model has been developed. The developed microscopic agent simulation model is a physical force based model similar to the social force model with forward and repulsion forces as the main force driver. However, the detail of the model is somewhat customized with inputs of the model. The repulsive force is added to guarantee collision avoidance. The developed model also uses the physical based variables that can be measured. The collision avoidance algorithm is influenced by existing algorithm flock which uses the steering behaviour to animate birds. It was revealed that the microscopic swarm model studies have been successfully applied to explore to the behaviour of microscopic agents flow by showing influenced three forces. The research was extended to fractal characteristics that share the characteristics of the fractal formation and agent paths. It is clearly shown that fractal could be used to approach the emerging swarm behaviour as we have produced the result that has sharing characteristics with crowd microscopic model.